1997
DOI: 10.1364/ao.36.009230
|View full text |Cite
|
Sign up to set email alerts
|

Design, implementation, and characterization of an optical power supply spot-array generator for a four-stage free-space optical backplane

Abstract: The design and implementation of a robust, scalable, and modular optical power supply spot-array generator for a modulator-based free-space optical backplane demonstrator is presented. Four arrays of 8 ϫ 4 spots with 6.47-m radii ͑at 1͞e 2 points͒ pitched at 125 m in the vertical direction and 250 m in the horizontal were required to provide the light for the optical interconnect. Tight system tolerances demanded careful optical design, robust optomechanics, and effective alignment techniques. Issues such as s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…A technique was therefore required to mount each of the OPS baseplates at 90° to the interconnect baseplate while maintaining alignment accuracy within correctable limits. In a previous implementation of an optical power supply to achieve this task [7] barrels were used to hold the optical components of the OPS. However, these were found lack sufficient insertion accuracy and were not suitable for the small dimensions of this system.…”
Section: Ops Baseplatementioning
confidence: 99%
“…A technique was therefore required to mount each of the OPS baseplates at 90° to the interconnect baseplate while maintaining alignment accuracy within correctable limits. In a previous implementation of an optical power supply to achieve this task [7] barrels were used to hold the optical components of the OPS. However, these were found lack sufficient insertion accuracy and were not suitable for the small dimensions of this system.…”
Section: Ops Baseplatementioning
confidence: 99%
“…Quarter-wave plates (QWP's) produced polarization changes at the appropriate places. The optical lenslet relays were designed to relay the beams using the maximum lensto-waist configuration [15]. Nominal component spacings are given in Table I.…”
Section: A Signal Beam Relaysmentioning
confidence: 99%
“…To simplify calculations, the focal length of was chosen to be 768 m since this was also the focal length for all signal lenslets. This yielded , which is the criterion for the maximum lens-to-waist distance [15]; another waist was located halfway between and , at a distance mm behind . At this halfway point, the beam radius can be calculated to be m. Similar calculations indicated that the focal length of had to be 1.87 mm in order to generate m. The nominal specifications of all components for the transmission of the and beams are given in Tables III and IV, respectively.…”
Section: B Optical Relay For Alignment Beams Andmentioning
confidence: 99%